2008
DOI: 10.1260/1475-472x.7.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Jet Noise by Staged Water Injection during Launch Vehicle Lift-Off

Abstract: Jet noise during the lift-off of a launch vehicle is complicated by the simultaneous flow of multiple jets, and their deflection by jet deflectors. Further, the presence of the launch pedestal, the service structure, and the moving vehicle itself, act as reflecting surfaces, which contribute to the noise environment. The present work involves the suppression of noise as measured at different parts of the launch vehicle in a small-scale replica of a full launch pad, for different locations of the vehicle along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Other technological applications include thrust-vectoring of high-speed vehicles (Perurena et al, 2009), solid-fuel rocket motors (Cai et al, 2003;Shimada et al, 2006), noise reduction in jet engines and rocket launch pads (Krothapalli et al, 2003;Ignatius et al, 2008;, operation of turbomachinery in particle-laden flows (Hamed et al, 2006), spray deposition (Dolatabadi et al, 2004;Samareh and Dolatabadi, 2008), mining safety (Ugarte et al, 2017), heterogeneous explosives , and drug-delivery systems using micro shock-tubes (Truong et al, 2006). Dense high-speed particle-laden flows also occur in nature.…”
Section: Background and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other technological applications include thrust-vectoring of high-speed vehicles (Perurena et al, 2009), solid-fuel rocket motors (Cai et al, 2003;Shimada et al, 2006), noise reduction in jet engines and rocket launch pads (Krothapalli et al, 2003;Ignatius et al, 2008;, operation of turbomachinery in particle-laden flows (Hamed et al, 2006), spray deposition (Dolatabadi et al, 2004;Samareh and Dolatabadi, 2008), mining safety (Ugarte et al, 2017), heterogeneous explosives , and drug-delivery systems using micro shock-tubes (Truong et al, 2006). Dense high-speed particle-laden flows also occur in nature.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Gas-turbines operating in regions with suspensions of sand particles in the air are subject to substantial degradation due to particle deposition on turbine blades ( Hamed et al, 2006 ). Water injection systems have been used to reduce sound intensity at rocket launch pads ( Ignatius et al, 2008 ), and it might be possible to utilize similar systems to reduce jet noise ( Krothapalli et al, 2003 ), which is especially important around air-crafts during takeoff. Shock wave interaction with particle clouds has been extensively studied over the last fifty years.…”
Section: Introductionmentioning
confidence: 99%
“…3 that the reduction in the noise level due to water injection is less sensitive to X=D e in the downstream region than in the upstream. It is known that the major noise source near the tip of the potential core is significantly affected by injection within the core [35]. Because the present range of X=D e is well within the potential core length, the reduction in the mixing noise is nearly insensitive to the injection location, as observed in the downstream direction.…”
Section: A Effect Of the Injection Locationmentioning
confidence: 89%
“…The two attenuation mechanisms observed were decrease of jet velocity by momentum transfer between liquid and gas phase and reduction of jet temperature due to partial vaporization of the injected water. The need to have sustained water injection near the rocket nozzle exit during the liftoff phase was recently reported by Ignatius et al [35]. In fact, multistage water injection was found to be very effective in the launch scenario.…”
Section: Introductionmentioning
confidence: 91%
“…Alternatively, for rocket launch or aircraft carriers, it is more practical to inject water from the impingement pad (launch pad or deflector). Ignatius et al 6,7 and Ragaller et al 8 have considered supersonic jets impinging on a perpendicular plate and have shown, experimentally, that injecting water from microjets through the impingement plate can reduce noise. They conjectured that water injection from the ground plane reduces the sources of sounds due to impingement.…”
Section: Introductionmentioning
confidence: 99%